DIURNAL CHANGES IN GAS EXCHANGE AND CHLOROPHYLL FLUORESCENCE IN GINKGO LEAVES UNDER FIELD CONDITIONS - Xian-Song Yang; Guo-Xiang Chen (Journal of Animal and Plant Sciences, 2015)
Gas exchange and chlorophyll a fluorescence were investigated to survey the diurnal changes in photosynthesis of ginkgo (Ginkgo biloba L.) leaves. The net CO2 assimilation rate showed a bi-peak diurnal pattern and midday depression of CO2 assimilation was observed at 13:00 h. Depression in CO2 assimilation at midday was not limited by stomatal factors, but rather non-stomatal factors because the loss in net CO2 assimilation rate was not followed by significant reductions in stomatal conductance and intracellular CO2 concentration. Midday depression in CO2 assimilation was associated with reversible inactivation of photosystem II reaction centers and increases of antenna heat dissipation in response to the strong midday sunlight. Performance index (PI) on absorption basis (PIabs) is more sensitive than the maximum photochemical efficiency of photosystem (PS) II (variable to maximum fluorescence ratio, Fv/Fm) to the changes in light and temperature. It is concluded that the dissipation of excessive excitation energy in the PS II may be the major protective mechanism to prevent the chloroplast from photodamage.
Keywords: Ginkgo biloba; chlorophyll fluorescence; gas exchange